English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

2(x + 3) = 6(x - 3)

Now if I am figuring this right, I can mow the 2 and 6 inside the parentheses which would make it (2 + 3) = (6 - 3) ?

2006-10-29 10:29:37 · 11 answers · asked by Advisor 1 in Science & Mathematics Mathematics

11 answers

2x + 6 = 6x - 18

2006-10-29 10:31:21 · answer #1 · answered by Anonymous · 0 0

3

2006-10-29 10:35:35 · answer #2 · answered by tina p 1 · 0 0

You should probably factor out the 2 and 6... thus getting 2x+6=6x-18, then subtract the 6x from the 2x and subtract the 6 from the 18 to get -4x=-24, then divide the -4 by -24 to get x= 6

2006-10-29 10:45:02 · answer #3 · answered by cool 2 · 0 0

2(x+3) = 2x+6 => 2x+6 = 0 Divide everything with 2
2x/2+6/2 =0 => x+3 = 0 => x= -3

2006-10-29 10:34:05 · answer #4 · answered by Anonymous · 0 0

What I would do is use the distributive property:
2(x+3)=6(x-3)
2x+6=6x-18
2x-6x=-18-6
8x=-24
x=-24/8
x=-3

2006-10-29 10:39:49 · answer #5 · answered by Rodney I 2 · 0 0

2(x + 3) = 6(x-3) multiply out giving

2x + 6 = 6x - 18 subtract 2x and add 18 to each side of the equation giving

24 = 4x

6 = x

2006-10-29 10:35:23 · answer #6 · answered by rosie recipe 7 · 0 0

I don't think you went about it right. You want to solve x, which in this case x should equal 6. Here's how I did it:
2x+6=6x-18 (you multiply 2 by x and 3 to remove the brackets, same with the other side of the equation-that's how you get 2x and 6).
Then you get the x's on the same side and the whole numbers on the same side. so you subtract 2x from the beginning to equal 0, and subtract it from the right side to get 4x. now add 18 to the right side to bring it to 0, then add it to the left side to equal 24. now we're left with 24=4x. divide 4x by 4 so to get x by itself, and divide 24 by 4 to get 6. x=6. you with me?

2006-10-29 10:39:11 · answer #7 · answered by Anonymous · 0 0

2x^3 - 6x^2 + 6x - 3 = 0 2x^3 -6x^2 + 6x = 3 finished the dice 2x^3 - 6x^2 + 6x + 2 = 5 ((2^a million/3)x +2^a million/3)^3 = 5 (2^a million/3)x + 2^a million/3 = 5^a million/3 (2^a million/3)x = 5^a million/3 - 2^a million/3 x = (5^a million/3 - 2^a million/3)/(2^a million/3) x = (5^a million/3)/(2^a million/3) - a million x^3 = 5/2 -a million x = a million.5^a million/3 JD

2016-12-05 08:41:22 · answer #8 · answered by mallie 4 · 0 0

not exactly if u move the 2 and 6 in u would multipy them in so instead u would get 2x+6=6x-18

then u would subtract 2x to 6x on the other side to get 6=4x-18

then u would add 18 to 6 on the other side to get 24=4x

u should be able to solve it from here divide 4 into both sides to get x=6

2006-10-29 10:34:40 · answer #9 · answered by mdmel 3 · 0 0

you have to use the distributive property first which would leave you with 2x + 6 = 6x - 18. then subtract 6 from both sides, giving you 2x=6x-24. now subtract 6x from both sides, giving you
-4x= -24. now divide both sides by -4, leaving you the
answer x=6

2006-10-29 10:55:37 · answer #10 · answered by P6890T 1 · 0 0

fedest.com, questions and answers